Dangke Hasil Olahan dari Susu Kuda Liar Sumbawa, Susu Sapi Sumbawa, dan Susu Kerbau Sumbawa: Dangke from Sumbawa Horse Milk, Sumbawa Cow Milk, and Sumbawa Buffalo Milk - Fathiaturrahma, Novi; Kusdianawati; Suharli, Lili (Anoa: Journal of Animal Husbandry, 2022)
Dangke is a local cheese product that is made enzymatically with the addition of papain enzyme through a heating process. Dangke is one of the innovations in processing food products (Sumbawa horse milk, Sumbawa cow’s milk, and Sumbawa buffalo milk) which has the potential to increase the selling power of milk. The research method begins with each milk being heated over low heat until the temperature reaches 60 - 70˚C while stirring to ensure all parts of the milk get an even heat. Furthermore, the addition of papain enzyme as much as 0.1% v/v. After that, the milk will form curd and whey. Curd was taken using a spoon and then drained using a sieve and put into a coconut shell mold and allowed to stand for a few minutes until it becomes a dangke product. Then the dangke quality was observed by looking at several indicators. The results showed that the processing of Sumbawa horse milk, Sumbawa cow’s milk, and Sumbawa buffalo milk succeeded in becoming dangke. Based on the indicators of dangke quality observation, the three types of milk were able to produce the same color and texture, namely milky white and soft texture. Meanwhile, for the indicators of aroma and length of clotting time, the three types of milk showed different results. Sumbawa wild horse milk requires ±9 minutes of clotting time, Sumbawa cow’s milk for ±10 minutes, and Sumbawa buffalo milk for ±8 minutes.